ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING PADA CV. ANEKA KARYA GLASS KARTASURA - Dian Raras Ati; Y. Djoko Suseno; Erni Widajanti (Universitas Slamet Riyadi, 2020)
CV. Aneka Karya Glass is a company that produces residential furniture made from glass and brass, one of the best selling products is a candle holder. Raw material control is needed to reduce raw material problems that often occur in the company. Problems in CV. Aneka Karya Glass is about controlling raw material inventories that occur due to excessive ordering which raises the high cost of savings. Material Requirement Planning (MRP) is a method of controlling raw materials proposed for the company. The techniques used are lot sizing including lot for lot (LFL), economic order quantity (EOQ), and order quantity period (POQ). The total cost obtained from the calculation of the lot sizing lot for lot (LFL) technique is IDR 14,400,000, economic order quantity (EOQ) of IDR 18,150,200, and the order quantity period (POQ) of IDR 14,400,000. So based on the results obtained, the company should implement the MRP method with the LFL or POQ lot sizing technique because the two techniques get the minimum total cost of IDR 14,400,000 so that they can save costs by 50%.